An ileal duplication cyst manifested as an ileocolic intussusception in an adult - Kim, Hyun-Soo; Sung, Ji-Youn; Park, Won Seo; Kim, Youn Wha (Turkish Journal of Gastroenterology, 2014)
Abstract An enteric duplication cyst presenting as enterocolic intussusception is an exceptional clinical entity. We herein report a rare case of an ileal duplication cyst that manifested as an ileocolic intussusception. A 19-year-old woman was hospitalized due to right upper quadrant pain. Colonoscopy revealed a polypoid mass protruding into the colonic lumen. Ultrasonography demonstrated intussusception with a teardrop-shaped cystic mass at the tip. Computed tomography also showed ileocolic intussusception with a 2.5 cm-sized round cystic mass at the tip of intussusceptum. Microscopically, the cystic wall consisted of a well-defined smooth muscle coat and heterotopic gastric mucosa, consistent with an enteric duplication cyst. This case highlights an ileal duplication cyst as an uncommon cause of adult ileocolic intussusception. To the best of our knowledge, this is the first case of enteric duplication cyst identified as a pathological lead point for enterocolic intussusception in an adult. Enteric duplication cysts should be included in the differential diagnosis of cystic-leading lesions for adult intussusceptions.